Using peer-ethnography to explore the health and well-being of college students affected by COVID-19 - Michelle Teti; Tyler W. Myroniuk; Grace Kirksey; Mariah Pratt; Enid Schatz (International Journal of Qualitative Studies on Health & Well-Being, 2023)
Purpose COVID-19 continues to infect and affect college-aged youth. We lack information about how students experienced the pandemic day-to-day and what they need for recovery, from their own perspectives. This study employed peer ethnography to explore student’s insights for current and future prevention and care. Methods A team of eight students were trained as peer ethnographers to observe and record conversations with their peers in 15-minute increments during the COVID-19 pandemic. Transcripts of 200 conversations were collated and analysed via theme analysis to identify patterns. Results Student conversations revealed dichotomous perspectives about COVID-19. Some students prioritized safety, captured via three themes—caution, rethinking routines, and protecting others. Other students struggled to follow prevention guidelines and took risks, also captured by three themes—parties, denial, and misinformation. A third category of themes captured the results of this dichotomy—tense campus relationships and a health leadership vacuum. Conclusions Our findings identify specific locations for intervention (e.g., off campus parties) and needed community collaborations (e.g., bars and universities) for COVID-19 and future pandemics. Our findings suggest that overarching approaches, like harm reduction or affirmation (versus shame), are helpful intervention frameworks. Findings also celebrate the value of peer-ethnography, to learn about pandemics and solutions from the ground up.